Retinol-binding protein-4 and nonalcoholic fatty liver disease - Hangkai Huang; Chengfu Xu; Yuanyuan Ji (Chinese Medical Journal, 2022)
Abstract. Nonalcoholic fatty liver disease (NAFLD) is becoming increasingly common as the global economy grows and living standards improve. Timely and effective preventions and treatments for NAFLD are urgently needed. Retinol-binding protein-4 (RBP4), the protein that transports retinol through the circulation, was found to be positively related to diabetes, obesity, cardiovascular disease, and other metabolic diseases. Observational studies on the association between serum RBP4 level and the prevalence of NAFLD found contradictory results. Some of the underlying mechanisms responsible for this association have been revealed, and the possible clinical implications of treating NAFLD by targeting RBP4 have been demonstrated. Future studies should focus on the predictive value of RBP4 on NAFLD development and its potential as a therapeutic target in NAFLD.